The Long Run Effects of Oil Prices on Economic Growth: The Case of Saudi Arabia - Foudeh, Musa (International Journal of Energy Economics and Policy, 2017)
This paper studies the long run effects of oil price growth rates (OS) on the economic growth of the Kingdom of Saudi Arabia (KSA). The empirical results of an ARDL model find a strong positive direct impact of OS on the GDP growth rates of KSA during the period 1995Q4-2015Q4. Despite the fact that China is the most important trading partner of KSA, OS doesn’t affect indirectly Saudi GDP growth rates. OS weakens the positive long run effect exercised on the GDP growth rates of KSA via trading with Japan. Although trading with South Korea and UK have negative significant effects on the Saudi GDP growth rates, OS has no possible indirect effect via trading with UK. But, it has a positive effect on the weighted GDP growth rates of S. Korea via trading with KSA. Trading with USA, India, Canada, France and Germany have no significant impacts on Saudi economy. Keywords: Saudi Arabia, Economic growth, Oil price effect, Autoregressive distributed lags model. JEL Classifications: O53, O40, C23